2012
DOI: 10.1080/02640414.2012.709265
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of the typical weekly in-season training load in elite junior soccer players

Abstract: We examined the typical weekly training load experienced by elite junior soccer players during the in-season competitive period. Altogether, eight under-14 (U14), eight under-16 (U16) and eight under-18 (U18) players were monitored over a 2-week period during the first month of the 2010-11 competitive season. This time period included one competitive match per week. Physiological loading was monitored using heart rate (HR) and ratings of perceived exertion (RPE). Training and match loads were calculated by mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
164
6
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 130 publications
(195 citation statements)
references
References 20 publications
18
164
6
7
Order By: Relevance
“…Such findings provide valuable information for interpreting meaningful betweenmatch changes in the players' different dimensions of perceived exertion. Given the relatively small range of matches included in our study (3)(4)(5)(6)(7)(8) we recognise that our thresholds for the interpretation of change may be an overestimation and acknowledge that further work in required in this area.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such findings provide valuable information for interpreting meaningful betweenmatch changes in the players' different dimensions of perceived exertion. Given the relatively small range of matches included in our study (3)(4)(5)(6)(7)(8) we recognise that our thresholds for the interpretation of change may be an overestimation and acknowledge that further work in required in this area.…”
Section: Discussionmentioning
confidence: 99%
“…3 Ratings of perceived exertion (RPE) provide a simple, noninvasive, inexpensive and valid method for measuring exercise intensity. 4,5 The limited available data demonstrate competitive match RPE's to be relatively stable measures in soccer players 6 and soccer referees 7 with between-match coefficients of variation (CV) of ~5%. This lack of variability, however, is observed despite high variability (between-match CV's 17-54%) for key measures of external load, in particular high-speed running and sprinting.…”
Section: Introductionmentioning
confidence: 99%
“…Milsom et al (2015) demonstrated that such populations typically 94 Therefore, the aims of the present study were two-fold: 1) to quantify the total daily 101 energy and macronutrient intakes of elite youth UK academy players of different ages 102 (U13/14, U15/16 and U18 playing squads) and 2) to quantify the daily distribution of 103 energy and macronutrient intake. In accordance with the higher absolute body masses 104 and training loads of the U18 squads (Wrigley et al, 2012), we hypothesised that this 105 squad would report higher absolute daily energy and macronutrient intakes in 106 comparison to the U13/14s and U15/16s. Furthermore, based on the habitual eating 107 patterns of both athletic and non-athletic populations (Mamerow et al, 2014), we 108 hypothesised that all squads would report an uneven daily distribution of 109 macronutrient intakes, particularly for daily protein intake.…”
mentioning
confidence: 89%
“…Ratings should refer to overall perceived exertion, which depends on many factors that are integrated into a kind of gestalt or configuration [11] and the scores should be therefore representative of both internal and external load [1,10]. However, the limited data that are available have demonstrated competitive soccer match RPE's to be stable measures in both players [12] and referees [13]. The lack of variability of these measures during competitive matches is of concern when attempting to understand the dose-response nature of matches given the high variability reported for measures of external load in soccer, in particular high-speed running and sprinting [3,4].…”
Section: Difficulties In Determining the Dose-response Nature Of Compmentioning
confidence: 99%